The Development of Online Module to Improve Chemistry Learning Outcomes in High Schools - Jumi Rahayu; Etin Solihatin; Rusmono Rusmono (Peneliti.net, 2022)
The objectives of this research are to determine the procedure for developing a suitable and effective Chemistry online module, as well as to know its feasibility and effectiveness in Chemistry learning in high schools. In order to achieve these objectives, the researcher use some research and development process by combining the Rowntree development model and the ILDF (Integrative Learning Design Framework). The Rowntree model is used to develop product in the form of draft module through preparation process, writing preparation and writing. The draft module is then designed and developed into an online module through the ILDF development model. ILDF consist of exploration, enactment and evaluation stages. The objects of this study are the students in Science class and the Chemistry teacher. Data were collected based on questionnaires, interviews, and student test results. Formative evaluation given by subject matter expert, learning design expert, media expert, as well as students shows that this module is suitable for learning. Furthermore, based on the T Test result on the students learning outcomes in the field test, there is significant difference between student learning outcomes before and after using the online module. The difference is indicated by the increase of the average learning outcomes up to 43.75 as the result of the online module use. Therefore, online module are very effective to improve student learning outcomes in Chemistry learning.